558 Programmed death (PD)-1 and PD-ligand-1 inhibitors in the treatment of non-small cell lung cancer: a systematic review of their efficacy and safety. (9th November 2020) - Lingohr-Smith, Melissa; Deitelzweig, Chelsea; Lin, Grace; Lin, Jay
Abstract : Background: Treatment advances have been made in non-small cell lung cancer (NSCLC) with the development and approval of programmed death (PD)-1 and PD-ligand 1 (PD-L1) inhibitors. PD-1 and PD-L1 inhibitors may be used as monotherapies or in combination with other agents and have been shown to improve NSCLC patient outcomes in clinical trials. We conducted a systematic search to compare the efficacy and safety of PD-1/PD-L1 inhibitors in the treatment of NSCLC. Methods: A systematic literature search of PubMed was conducted to identify phase III clinical trials in which the efficacy of PD-1/PD-L1 inhibitors in the treatment of NSCLC was evaluated. PD-1 inhibitors included nivolumab and pembrolizumab; PD-L1 inhibitors included atezolizumab, avelumab, and durvalumab. Patient characteristics and efficacy data were extracted. Results: Sixteen phase III clinical trials were identified (nivolumab=4; pembrolizumab=5; atezolizumab=5; avelumab=1; durvalumab=1). Across the 3 nivolumab monotherapy trials (n=638; median ages: 61–63 years), median progression-free survival (PFS) ranged 2.3–4.2 months; response rates ranged 19%-26%; grade 3/4 adverse events occurred in 7%-18% of patients. Nivolumab in combination with iplimumab (n=583; median age: 64 years) had a median PFS of 5.1 months and response rate of 33%; grade 3/4 adverse events occurred in 33% of patients. Across the 3 pembrolizumab monotherapy trials (n=1, 481; median ages: 63–64 years), median PFS ranged 3.9–10.3 months; response rates ranged 18%-45%; grade ≥3 adverse events occurred in 13%-27% of patients. In the 2 pembrolizumab combination therapy trials (n=688; median ages: 65 years), median PFS ranged 6.4–8.8 months; response rates ranged 48%-58%; grade ≥3 adverse events occurred in 67%-70% of patients. In the 4 atezolizumab combination therapy trials (n=1, 486; median ages: 63–64 years), median PFS ranged 6.3–8.3 months; response rates ranged 47%-63.5%; grade 3/4 adverse events occurred in 54%-73% of patients. In the 3 monotherapy trials of atezolizumab (n=613; median age: 63 years), avelumab (n=396; median age: 64 years), and durvalumab (n=476; median age: 64 years), the median months of PFS were 2.7, 2.8, and 17.2, respectively; response rates were 14%, 15%, and 30%, respectively; grade ≥3 adverse events occurred in 15%, 10%, and 30.5% of patients, respectively. Conclusions: Although treatment responses varied, most of the evaluated PD-1/PD-L1 inhibitors were associated with a clinical benefit for NSCLC trial patients. Generally, treatment efficacy was greater with combination therapies, but adverse events occurred more frequently. Innovations in the targeting/personalization of PD-1/PD-L1 combination therapies will likely lead to improved NSCLC patient outcomes and further research is needed in this regard.